الورم الاذيني المخاطي - معروف, باسم (Latakia University Journal -Medical Sciences Series, 2017)
سيدة عمرها 60 عاما , اجرت استشارة قلبية من اجل ارتفاع التوتر الشريانيالاستجواب:المريضة غير عرضية لديها عوامل خطورة القلبية التالية 1. التدخين (1) باكيت /اليوم منذ 40 عام و2. ارتفاع توتر شرياني اساسي مكتشف منذ 20 عام معالج بشكل غير منضبط لاسوابق مرضية او جراحية او عائلية الفحص القلبي الوعائي :الضغط /145 90 النبض /80 الدقيقةلا نفخات قلبية ,لا اصوات اضافية , النبض المحيطي محسوس ,لاوذمات انطباعية ,لا احتقان وداجي تخطيط القلب الكهربائي ECG :نظم جيبي ,لايوجد اضطراب في عودة الاستقطاب ,لا اضطراب في النقل صورة الصدر: ضمن الطبيعي لمريض مدخن ,الفحوص الدموية والكيماوية المتممة : طبيعية ايكو القلب عبر الصدر :اظهر وجود كتلة شاغله لحيز في الاذينة اليسرى , تقيس 4 * 3.5 سم مفصصة غير ملساء غير متجانسة صدويا ملتصقة على الحاجز الاذيني بقاعدة عريضة تمتد من الحفرة البيضية نحو سقف الاذينة اليسرى بمحازات الوريد الاجوف العلوي في الجانب الايمن ايكو القلب عبر المري: لم يظهر معطيات اكثر, الا انه اظهر عدم وجود اورام مرافقة في الاجواف الاخرى بشكل اوضحالقثطرة القلبية : اظهرت وجود امهات دم متعددة على الشرايين الاكليلية مع تضيق 50 % على القطعة الاولى من الشريان الاكليلي الامامي النازل تم تحويل المريضة الى قسم جراحة القلب حيث تم استئصال الورم بنجاح , التشريح المرضي اظهر انه ورم اذيني مخاطي سليم A-60 years old woman, did cardiac consulting for hypertensionInterrogation: The patient is asymptomatic she has the following cardiac risk factors Smoking (1) Packet / day for 40 years and arterial hypertension for 20 years ago , uncontrolledshe has not surgical or medicals antecedents Cardiovascular examination: BP: 14,5\90, pulse : 80\ M, No murmurs no additional voices ,peripheral pulse are palpable, no edema , not congestion jugular. Twelve-lead electrocardiography showed sinus rhythm,there are not troubles of repolarization, no of conduction Chest radiography showed normal cardiac silhouette, blood tests are normals Echocardiography throw chest : showed the presence a mass in the left atrium, measuring 4 x 3.5 cm lobed ,smooth heterogeneous, attached to the atrial septum , it has broad base extends from the fossa ovalis to the roof of the left atrium beside superior vena cava to the right sideEchodppler throw esophagi does not appear more data, but it showed absence of anthor tumors in other cardiac cavities Cardiac catheterization: showed the presence of multiple aneurysms on the coronary arteries with stenosis of 50% on the first segment of the anterior descending coronary artery(LAD)The patient has been transferred to the Department of Cardiac Surgery, where the tumor was removed successfully and Histopathology showed that it is an aterial myxoma ( benign tumor)